On-farm evaluation of cassava clones using the triadic comparison of technology options approach - Nanyonjo, Ann Ritah; Angudubo, Stephen; Iragaba, Paula; Brown, David; Nuwamanya, Ephraim; Esuma, Williams; Ozimati, Alfred; Wembabazi, Enoch; Kanaabi, Michael; Muhumuza, Nicholas; Bayiyana, Irene; van Etten, Jacob; et al. (Wiley, 2024)
The triadic comparison of technology options (tricot) approach to participatory varietal selection has been demonstrated to scale out the on‐farm testing of elite candidate crop varieties. In this study, we evaluated elite clones of cassava (Manihot esculenta Crantz) using the tricot approach. We sought to (1) synthesize on‐farm trial data from two cycles evaluating different sets of elite cassava clones; (2) assess the agronomic performance of elite cassava clones considering sociodemographic and climatic factors; and (3) assess the performance of elite cassava clones for both agronomic and food quality traits. The study involved 10 districts in Uganda, two cycles/seasons of evaluation, 20 elite cassava clones, one check variety, and 294 men and 320 women farmers. Our results indicate that the agronomic performance of elite cassava clones was influenced more by geographic than sociodemographic factors. Our analysis identified the number of days with rainfall higher than 20 mm as the most influencing climatic factor over agronomic performance. Further, the study identified superior elite cassava clones UG110164, UGC14170, and UG120193 as promising candidate varieties for release, targeting food products. Overall, our study emphasizes the important contribution of end‐users to crop improvement and provides insights into use of tricot on‐farm testing methodology to evaluate elite cassava clones during cassava variety development in Uganda, which can be used to support decision making for variety release.